Hot Love and Cold People. Sexual Liberalism as Political Escapism in Radical Sweden - Carl Marklund (NORDEUROPAforum - Zeitschrift für Kulturstudien, 2009)
The longstanding association of the “North” with “rationality” on the one hand and “Sweden” with “sex” on the other fulfilled a particular role in the philosophical geography of the radical 1960s and 1970s. By looking at works by Susan Sontag and Roland Huntford, this article proposes that Sweden could aid both radicals and conservatives in making sense of the “Western” heritage in an era of fundamental cultural change. While Sontag regarded sexual liberalism as part of a deeper fear of conflict, Huntford saw Swedish sexual liberalism as a result of political control. Both Sontag and Huntford agreed that in the end, the Swedes were not “authentically” liberated. This kind of “septentrionalism” helped Sontag and Huntford to construct a cultural compass with a negative North pole of cold, rational, and unnatural “modernity” as representative of elements which they both sought to combat in their respective home countries.